PEMANFAATAN PROBIOTIK DALAM PEMBUATAN RANSUM UNTUK MENINGKATKAN EFISIENSI PENGGUNAAN RANSUM PADA TERNAK NON RUMINANSIA DI DESA MEDAHAN GIANYYAR - NI MADE SUCI SUKMAWATI; A.A.A. SRI TRISNADEWI; NI LUH PUTU SRIYANI; I PUTU ARI ASTAWA; DESAK PUTU MAS ARI CANDRAWATI; I KETUT MANGKU BUDIASA (Buletin Udayana Mengabdi, 2008)
This activity on the service to people in Medahan Village, Blahbatuh Sub District, Gianyar District Aimed to improveded soft skill of farmers in applied of probiotic matter used and feed formulation for improveded of feed convertion for to increased of feed conversion on ruminant animal on Week, 7th October 2007 with following twenty fife farmers. The method of were lecture and training about applied probiotic matter and feed formation for non ruminant animal. Evaluated method to do on praction phase, action phase, and understand to realize phase. The result of the activity showed that praction phas eto get people response was 75 percentage, people response on action phase about applied of proiotic matter and feed formulation for non ruminant animal were 85% on understand phase that with lecture and apply about its happened undestand response to increased from 50 until 80 pecentage. It was concluded that the response of farmres to applied of probiotic matter used and feed formation for improveded of feed conversion for to increased of feed conversion on non ruminant animal were higher (70-85 percentage).